Invasive fungal infections in pediatric patients with central nervous system tumors: novel insights for prophylactic treatments? - Dassi, Natália; Cappellano, Andrea Maria; Silva, Adriana Maria Paixão de Sousa da; da Silva, Nasjla Saba; Carlesse, Fabianne Altruda de Moraes Costa (Frontiers in Oncology, 2023)
Background and aims: Invasive fungal diseases (IFDs) pose significant morbidity and mortality risks, especially among pediatric patients with neoplastic diseases.However, there is a notable lack of data concerning patients with central nervous system (CNS) tumors. Considering vulnerability factors to infections such as neutropenia, corticosteroids, chemotherapy, surgical interventions and others, this study aims to evaluate the incidence of IFDs in pediatric patients with CNS tumors and determine appropriate indications for prophylactic measures. This is a single-center, retrospective study, conducted between 2011-2022 at the Pediatric Institute of Oncology (IOP-GRAACC-UNIFESP). Results: Thirty-eight IFDs were diagnosed among 818 children with CNS malignancies (4,6%). The mean age was 3.5 years (0.4-28y), 22 males (57.9%). Embryonal tumors (18/38, 47.3%) were the most prevalent CNS tumors, followed by low-grade gliomas (13/38, 34.2%). All episodes met EORTC IFD criteria, 36/38 (94.7%) proven.Invasive yeast infections (33/36, 91.6%), predominantly Candida (30/33, 90.9%), were the most frequent diagnosis. Twenty-five (25/38, 65.8%) were under chemotherapy, 13 of whom had embryonal tumors, 11 were infants under the Head Start scheme, which entailed a high incidence of IFD in this group (11/58, 18.9%). Thirteen (13/38, 34.2%) patients were submitted to neurosurgery, mostly ventricular peritoneal shunt (10/13, 76.9%). Nine (9/38, 23.7%) were with prolonged use of corticosteroids, eight associated with neurosurgery. Conclusion: Routine systemic antifungal prophylaxis based solely on diagnosis for low-risk cases is not recommended. Evaluating patient-and treatment-specific risk factors is crucial as infants undergoing high-dose chemotherapy with expected neutropenia and patients requiring prolonged corticosteroid therapy alongside neurosurgery procedures.